Pandangan Holistik Manusia Sebagai Akar Pengembangan Inovasi Konseling - Hasan Bastomi (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2018)
Humans are holistic beings, aspects of human life can be classified into four main aspects, namely physical, mental, social, and spiritual. In this paper aims to find out the concept of holistic guidance and counseling services as an innovation in the field of counseling. As a counselor should make holistic counseling as a foundation for the development of counseling innovation, so that in counseling practice can view human as holistic in terms of humanity, problem complexity and cooperation among counselor team since searching data, and look for conclusions on the data (diagnosis), create a plan of action (treatment planning), and perform treatment measures (treatment), evaluation process, until termination (termination).